THE LEGACIES OF THE NATIVES LAND ACT OF 1913 - Hall, Ruth (Scriptura, 2014)
Looking back at the century since the promulgation of the Natives Land Act, it could be argued that it shaped the trajectories of most South Africans’ lives. It expelled black people from the land into crowded reserves and formed the cornerstone of the migrant labour system through which accumulation of wealth in white-owned mines, farms and factories followed. Far from unravelling this history of dispossession, the land reform process has merely dabbled at its edges while the inequalities it set in place have in some ways been further aggravated since 1994. Four legacies of the Act are identified: the material legacy of poverty and inequality in the divided countryside but also the displaced legacy of urban poverty and inequality; the social and spiritual legacy of division, invisibility and failed reconciliation; and a political legacy of legal pluralism and dualistic governance that denotes zones of tradition or custom, distinct from the rest of the country. In this context, the church needs to reflect, not only on its mixed involvement in dispossession and resistance to it in the past, but also on its role in dismantling the structures of poverty and inequality, social and spiritual division, invisibility and dualistic governance.